Social and ecological history of the Pyrenees : state, market, and landscape - Vaccaro, Ismael; Beltran, Oriol (New frontiers in historical ecology., 2010)
This major work of historical ecology significantly advances the integration of research on natural and social systems, contributing important lessons for contemporary resource policy and management.